Evaluation of Water Productivity for Different Rice Based Cropping Sequences in Gazipur (Bangladesh Rice Journal, 2015)
Declining trend of water resources for Boro rice cultivation in different areas lead researchers and farmers to find out alternate cropping sequences. A field experiment was conducted in silty clay soil to evaluate the water productivity and profitability of different rice based cropping sequences during 2006-07 to 2008-09 at the BRRI farm, Gazipur. Three cropping sequences viz T. Aman-Boro-Fallow, T. Aman-Wheat-Mungbean and T. Aman-Potato-Mungbean and three water regimes assigned differently for each component crops were evaluated in a split-plot design. Among the cropping sequences, T. Aman-Potato-Mungbean with one irrigation at vegetative and two in reproductive stages for T. Aman rice, three irrigation each at 20, 40 and 60 DAS for potato and two irrigations for mungbean gave significantly higher rice equivalent yield of 33.40, 22.59 and 28.44 t ha-1 in 2006-07, 2007-08 and 2008-09 respectively. The variation in yield equivalence was mostly governed by potato crop grown in Rabi season. The maximum water productivity of 23.41, 18.57 and 23.62 kg ha-1 mm was recorded in rainfed for T. Aman and mungbean and one irrigation for potato in 2006-07, 2007-08 and 2008-09 respectively. The higher yield of potato raised the water productivity in T. Aman-Potato-Mungbean cropping sequence. Maximum net return of Tk 2,28,056, 2,75,389 and 4,05,986 and maximum BCR values from T. Aman-Potato- Mungbean cropping sequence with T3 irrigation regimes of the respective crops during 2006-7, 2007-8 and 2008-9 respectively indicated that the sequence would be suitable for getting higher yield and economic return.Bangladesh Rice j. 2015, 19(1): 41-48